Green technology wrist band with patient identification near field communication (NFC) or radio frequency identification (RFID) security features - Dahwi M.M.M.; Ismail W.; Afandi R.R.; Husin A.; Hassan R.; Bahari M. (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA